Ceramic Crucible Corrosion by Heavy Metal Oxide Glasses, Part II: Diffusion Study - Dos Santos, Iêda Maria Garcia; Moreira, Rafael Carlos Martins; De Souza, Antônio Gouveia; Leite, Edson Roberto; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (My University, 2003)
Due to their low cost and high resistance to corrosion, ceramic crucibles can be used for the melting of PBG glasses (PbO-BiO 1.5GaO 1.5). These glasses present good window transmission from ultra-violet to infrared, making their use as optical fibres promising. However, their disadvantage is the high reactivity, leading to the corrosion of different crucibles, including gold and platinum ones. In this work, the corrosion of Al 2O 3, SnO 2 and ZrO 2 crucibles after melting at temperatures varying from 850 to 1000°C, was evaluated by Scanning Electronic Microscopy (SEM) in conjunction with microanalysis by EDS. The lead diffusion profile in the crucible material was obtained. Diffusion coefficients were calculated according to the Fick and Fisher theories. Results indicated that the different crucibles presented similar behaviour: in the region near the interface, diffusion occurs in the volumetric way and in regions away from the interface, diffusion occurs through grain boundary.
Keywords: Al 2O 3; Ceramic crucibles; Diffusion; PbO-BiO 1.5-GaO 1.5 glasses; SnO 2; ZrO 2; Alumina; Ceramic materials; Corrosion protection; Glass; Grain boundaries; Lead compounds; Microanalysis; Zirconia; Crucibles